Relapsing Klebsiella Pneumoniae Liver Abscesses in a Non-Asian Diabetic Man - Neves, Z (2017)
The Klebsiella pneumoniae invasive syndrome, first described in Asia, is being reported in other parts of the world. It causes liver abcsesses, with or without extrahepatic lesions. Diabetes mellitus is the most common hosts’ underlying condition. It’s frequent among asian people, even outside Asia, appearing to exist genetic factors, not yet established, increasing the risk. We present a case of a 55-year-old portuguese white diabetic man, who had a previous hospital admittion due to Klebsiella penumoniae pneumonia and a two-week latter diagnosis of liver abcsess. 4 years latter he was readmitted with nausea, chills, fever and myalgias. He had elevated inflammatory markers and the CT-scan showed 2 liver abscesses. Klebsiella pneumoniae was isolated in blood and antibiotics were given with complete clinical and imaging resolution. We present this case of relapsing Klebsiella pneumonia liver abscesses in a non-asian man emphasizing the growing incidence of this condition in Europe.